Common variants in Alzheimer’s disease and risk stratification by polygenic risk scores - Itziar de Rojas (Nature Portfolio, 2021)
Known genetic loci account for only a fraction of the genetic contribution to Alzheimer’s disease. Here, the authors have performed a large genome-wide meta-analysis comprising 409,435 individuals to discover 6 new loci and demonstrate the efficacy of an Alzheimer’s disease polygenic risk score.